Reconstruction of pressure sores with flap in Bharatpur Hospital, Chitwan: A retrospective study - Suresh Kumar Pradhan; Srijana Dwa; Santosh Kumar Yadav (Asian Journal of Medical Sciences, 2025)
Background: Pressure sores (pressure ulcers) are a significant concern in healthcare, particularly among individuals with limited mobility. Surgical reconstruction using flaps is a common intervention for severe cases. Aims and Objectives: The aims and objectives of the study are to explore the epidemiological profile, complications, and associated factors in flap reconstruction for pressure sores. Materials and Methods: A retrospective analysis was conducted on 58 patients who underwent flap reconstruction for pressure sores at Bharatpur Hospital. Sociodemographic variables, comorbidities, smoking status, and surgical techniques were recorded. Post-operative complications were assessed, and statistical analyses, including Chi-square tests and logistic regression, were employed to explore associations. Results: The patient population was predominantly middle-aged (35–49 years), predominantly male, with head injuries being the leading cause of pressure sores. Ischial region ulcers were most prevalent. Post-operative complications included dehiscence, deep surgical site infection, and serious fluid accumulation. Smoking status was significantly associated with complications (P<0.001). Age also showed a significant correlation (P≤0.001), with the middle-age group experiencing fewer complications. No significant gender-based differences were observed in complication rates (P=0.572). Conclusion: This study highlights the demographic and clinical characteristics of patients undergoing flap reconstruction for pressure sores. It recommends emphasizing smoking cessation programs and conducting careful risk assessments for older patients. A multidisciplinary approach is essential for effective pressure sore management. Further prospective studies are needed to validate these findings and enhance patient care strategies.